Role of Claudin Proteins in Regulating Cancer Stem Cells and Chemoresistance-Potential Implication in Disease Prognosis and Therapy - Gowrikumar, Saiprasad (Int J Mol Sci, 2019)
Claudins are cell–cell adhesion proteins, which are expressed in tight junctions (TJs), the most common apical cell-cell adhesion. Claudin proteins help to regulate defense and barrier functions, as well as differentiation and polarity in epithelial and endothelial cells. A series of studies have now reported dysregulation of claudin proteins in cancers. However, the precise mechanisms are still not well understood. Nonetheless, studies have clearly demonstrated a causal role of multiple claudins in the regulation of epithelial to mesenchymal transition (EMT), a key feature in the acquisition of a cancer stem cell phenotype in cancer cells. In addition, claudin proteins are known to modulate therapy resistance in cancer cells, a feature associated with cancer stem cells. In this review, we have focused primarily on highlighting the causal link between claudins, cancer stem cells, and therapy resistance. We have also contemplated the significance of claudins as novel targets in improving the efficacy of cancer therapy. Overall, this review provides a much-needed understanding of the emerging role of claudin proteins in cancer malignancy and therapeutic management.